Communal Meaning and Religious Boundaries: Lived Religion at the Negeri Church in Waraka, Central Maluku - Lailossa, Petra; Lattu, Izak Yohan Matriks; Ludji, Irene (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Sacred places are often understood primarily through their institutional ownership and formal religious functions. Less attention has been paid to how a sacred place associated with one religious tradition may acquire wider communal meaning without losing its particular religious identity. This study examines how Protestant, Muslim, and Catholic residents of Negeri Waraka interpret the Negeri Church and how collective memory, the Nazar Negeri, customary authority, and religious boundaries shape its social meaning. The study used a qualitative, focused ethnographic approach. Fieldwork was conducted in Waraka, Central Maluku, from December 2025 to January 2026 and involved 16 purposively selected participants, including customary authorities, religious leaders, village representatives, and residents from the three religious communities. Data were collected through semi-structured interviews, open observer-as-participant fieldwork, field notes, photographs, and relevant documents and were analyzed thematically. The findings show that the church remains a Protestant liturgical space while also functioning as a material reference point for Waraka’s collective history and communal identity. The annual Nazar Negeri connects the Raja’s house and the church through differentiated participation: Protestant residents retain liturgical authority, whereas Muslim and Catholic residents participate through customary and civic roles. The continuity of this arrangement depends on collective memory and the mediating authority of the Raja, Saniri Negeri, and religious leaders. The Waraka case demonstrates that the communal significance of a sacred place does not require the erasure of religious boundaries. Instead, shared meaning is produced through negotiated participation, customary belonging, and the continuing recognition of religious difference.